Pengaruh CTO dan DAR terhadap ROA pada Perusahaan Industri Dasar dan Kimia di BEI Periode 2014-2018 - Novia Wandasari; Dimas Sumitra Danisworo; Djoni Djatnika (Indonesian Journal of Economics and Management, 2021)
This research aims to determine the influence of CTO and DAR to ROA.The population used is the basic and chemical industry companies on IDX for the 2014-2018 period amounted to 58 companies. Sampling withdrawal using purposive sampling technique and there are 13 samples of companies in the basic industry and chemical as samples that are sample of this research. The data used is secondary data from annual report that has been published by the website of each company. The data analysis technique used is the data regresion analysis panel with Eviews software tools version 10. The result show that Cash Turnover does not have a significant effect on ROA, DAR has a negative and significant effect on ROA, as well as Cash Turnover and DAR simultaneously have a significant effect on ROA with R-Square value 68,66%.